Bertonio and Aymara suffixes - Huayhua Pari, Felipe (2003)
The paper presents the Aymara suffixes used by Bertonio and compares them with the current suffixes. The suffixes have been classified into derivational, inflectional and independent suffixes, both in nouns and verbs. The author describes processes of grammaticalization as well as lexicalization. The study aims at the revitalization of the language.